The impact of lncRNA-GAS5/miRNA-200/ACE2 molecular pathway on the severity of COVID-19 - Ayeldeen, Ghada; Shaker, Olfat G; Amer, Eman; Zaafan, Mai A; Herzalla, Mohamed R; Keshk, Mofida A; Abdelhamid, Amr M (Current medicinal chemistry, 2024)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is responsible for coronavirus disease (COVID-19), potentially has severe adverse effects, leading to public health crises worldwide. In COVID-19, deficiency of ACE-2 is linked to increased inflammation and cytokine storms via increased angiotensin II levels and decreased ACE-2/Mas receptor axis activity. MiRNAs are small sequences of noncoding RNAs that regulate gene expression by binding to the targeted mRNAs. MiR-200 dysfunction has been linked to the development of ARDS following acute lung injury and has been proposed as a key regulator of ACE2 expression. LncRNA growth arrest-specific transcript 5 (GAS5) has been recently studied for its modulatory effect on the miRNA-200/ACE2 axis. The current study aims to investigate the role of lncRNA GAS5, miRNA-200, and ACE2 as new COVID-19 diagnostic markers capable of predicting the severity of SARS-CoV-2 complications. A total of 280 subjects were classified into three groups: COVID-19-negative controls (n=80), and COVID-19 patients (n=200) who required hospitalization were classified into two groups: group (2) moderate cases (n=112) and group (3) severe cases (n = 88). The results showed that the serum GAS5 expression was significantly down-expressed in COVID-19 patients; as a consequence, the expression of miR-200 was reported to be overexpressed and its targeted ACE2 was down-regulated. The ROC curve was drawn to examine the diagnostic abilities of GAS5, miR-200, and ACE2, yielding high diagnostic accuracy with high sensitivity and specificity. lncRNA-GAS5, miRNA-200, and ACE2 panels presented great diagnostic potential as they demonstrated the highest diagnostic accuracy for discriminating moderate COVID-19 and severe COVID-19 cases.